The cause of predominance and its impact on the structure of the word in the Arabic language - Alfugara, Saif; Bialeajid, Maryam (Al-Adab Journal, 2023)
The research studies the reasoning for the predominance of the morphology level in the Arabic language, we discussed in it the concept of the cause of predominance, and the position of scholars regarding it in linguistic analysis, and the manifestations of this defect in the morphology level in the Arabic language, and manifestations of this reason in the interpretation of the structure of the word in Arabic, in order to clarify its effect in clarifying, and In the chapter on plural, feminine, masculine, lineage and diminutive, and various morphological issues. The problem of the research emerged from the prevalence of the cause of predominance in this study, the researcher sought to answer the research questions in knowing the concept of the cause of dominance, what is the position of scholars on it? What are the manifestations of its prevalence in linguistic analysis in the morphology? The researcher adopted the descriptive analytical method in the research by collecting and analyzing the topics of the cause of predominance in the study strongly in the linguistic lesson with the absence of specialized studies in it, the importance of the study comes in clarifying this illness and its impact on the language.